Method for fabricating the heater buried plane waveguide path type of an optical switch - CHUNG; MYOUNG-YOUNG; CHOI; TAE-GOO; SIN; JANG-UK; SIM; JAE-GI (1997)
The present invention relates to a method for fabricating the plane waveguide path type of the heater buried optical switch, and it exposes the thin film heater removing the second clad layer to speed the heat radiation of the thin film heater by forming flatly the first clad layer having the thin thickness of about 5-10 mu m on the channel waveguide path on which the channel waveguide path is formed on the lower clad layer, and forming the second upper clad layer in the thickness of about 15-20 mu m on the first clad layer and the thin film heater after the thin heater having the line width of about two times as compared with these of the channel waveguide path is formed at the channel waveguide path and the corresponding portion on the first upper clad layer. Therefore, the crosstalk between the neighboring channel waveguides can be protected since the heat generated in the thin film heater inhibits to transmit the neighboring channel waveguide paths, and the switch velocity accelerates as speeding the heat transmitting velocity, and it can operate at the low operational power.